Arabidopsis APx-R Is a Plastidial Ascorbate-Independent Peroxidase Regulated by Photomorphogenesis - Fernanda Lazzarotto; Khadija Wahni; Maiara Piovesana; Felipe Maraschin; Joris Messens; Marcia Margis-Pinheiro (MDPI AG, 2021)
Peroxidases are enzymes that catalyze the reduction of hydrogen peroxide, thus minimizing cell injury and modulating signaling pathways as response to this reactive oxygen species. Using a phylogenetic approach, we previously identified a new peroxidase family composed of a small subset of ascorbate peroxidase (APx) homologs with distinguished features, which we named ascorbate peroxidase-related (APx-R). In this study, we showed that APx-R is an ascorbate-independent heme peroxidase. Despite being annotated as a cytosolic protein in public databases, transient expression of AtAPx-R-YFP in Arabidopsis thaliana protoplasts and stable overexpression in plants showed that the protein is targeted to plastids. To characterize APx-R participation in the antioxidant metabolism, we analyzed loss-of-function mutants and AtAPx-R overexpressing lines. Molecular analysis showed that glutathione peroxidase 7 (GPx07) is specifically induced to compensate the absence of APx-R. APx-R overexpressing lines display faster germination rates, further confirming the involvement of APx-R in seed germination. The constitutive overexpression of AtAPx-R-YFP unraveled the existence of a post-translational mechanism that eliminates APx-R from most tissues, in a process coordinated with photomorphogenesis. Our results show a direct role of APx-R during germinative and post-germinative development associated with etioplasts differentiation.